2016
DOI: 10.1186/s12905-016-0304-8
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of cervical intraepithelial lesions after thermo-coagulation in HIV-positive and HIV-negative Nigerian women

Abstract: BackgroundThe burden of cervical cancer remains huge globally, more so in sub-Saharan Africa. Effectiveness of screening, rates of recurrence following treatment and factors driving these in Africans have not been sufficiently studied. The purpose of this study therefore was to investigate factors associated with recurrence of cervical intraepithelial lesions following thermo-coagulation in HIV-positive and HIV-negative Nigerian women using Visual Inspection with Acetic Acid (VIA) or Lugol’s Iodine (VILI) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 39 publications
4
40
1
Order By: Relevance
“…A recent systematic review, and subsequent publications, suggest that HIV‐infected women are more likely to have treatment failures/recurrent disease, but the evidence for each treatment modality is very limited. The most likely explanation is that HIV‐infected women have larger lesions due to immune suppression and therefore the lesion margins are not clear, leading to failure/recurrence. Does the healed epithelium following ablation allow for effective monitoring and diagnosis of recurrent (untreated) disease? Placed into context, if a treatment is 90% effective in treating CIN 2–3, the treated cohort has a prevalence of 10% CIN 2–3, which is several fold higher risk than the general population from which they were screened.…”
Section: Future Research On Treatment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review, and subsequent publications, suggest that HIV‐infected women are more likely to have treatment failures/recurrent disease, but the evidence for each treatment modality is very limited. The most likely explanation is that HIV‐infected women have larger lesions due to immune suppression and therefore the lesion margins are not clear, leading to failure/recurrence. Does the healed epithelium following ablation allow for effective monitoring and diagnosis of recurrent (untreated) disease? Placed into context, if a treatment is 90% effective in treating CIN 2–3, the treated cohort has a prevalence of 10% CIN 2–3, which is several fold higher risk than the general population from which they were screened.…”
Section: Future Research On Treatment Methodsmentioning
confidence: 99%
“…The authors reported no serious adverse effects, and pain was reported as minor by most women—a single woman reported significant pain. Oga et al . reviewed studies that had used thermal coagulation in VIA‐based screen‐and‐treat programs at six sites in Nigeria, which included both HIV‐positive and HIV‐negative women.…”
Section: Experience With Thermal Coagulationmentioning
confidence: 99%
“…In SSA, the six most common types of HPV are oncogenic types 16, 18, 35, 45, 33, and 52 [14]. Immunologic and virologic HIV control are significant co-factors in the persistence, and progression of HPV infection to pre-malignant lesions and ICC [11, 15, 16]. The use of cART, however, may not completely reverse the oncogenic potential of HPV especially if early malignant changes begin to take place while CD4 counts are low [15].…”
Section: Cervical Cancermentioning
confidence: 99%
“…In a meta-analysis of the performance of VIA, recurrence after treatment was higher among HIV-infected compared with HIV-uninfected women but morbidity from treatment was similar (19). Among Nigerian HIV-infected women participating in a see-and-treat program and treated for cervical disease with thermal coagulation, there was no statistically significant difference in recurrence between HIV-infected and HIV-uninfected women (20). However among HIV-infected women the risk of recurrence was highest among those with lower CD4 levels.…”
Section: Introductionmentioning
confidence: 99%